Gastroprotective Effects of L‐Lysine Salification of Ketoprofen in Ethanol‐Injured Gastric Mucosa. Issue 4 (April 2015) - Cimini, Annamaria; Brandolini, Laura; Gentile, Roberta; Cristiano, Loredana; Menghini, Paola; Fidoamore, Alessia; Antonosante, Andrea; Benedetti, Elisabetta; Giordano, Antonio; Allegretti, Marcello
Abstract Ketoprofen L‐lysine salt (KLS), a NSAID, is widely used for its analgesic efficacy and tolerability. L‐lysine salification was reported to increase the solubility and the gastric absorption and tolerance of ketoprofen. Since the management of NSAIDs gastrotoxicity still represents a major limitation in prolonged therapies, mainly when gastric lesions are present, this study investigated the gastro‐protective activity of L‐lysine by using a well‐established model of gastric mucosa injury, the ethanol‐gastric injury model. Several evidences show that the damaging action of ethanol could be attributed to the increase of ROS, which plays a key role in the increase of lipid peroxidation products, including malonyldialdehyde and 4‐hydroxy‐2‐nonenal. With the aim to unravel the mechanism of L‐lysine gastroprotection, cellular MDA levels and 4‐HNE protein adducts as markers of lipid peroxidation and a panel of key endogenous gastro‐protective proteins were assayed. The data obtained indicate a gastroprotective effect of L‐lysine on gastric mucosa integrity. J. Cell. Physiol. 230: 813–820, 2015. © 2014 Wiley Periodicals, Inc.